2014
DOI: 10.1038/srep03642
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Metamaterial Superlens for Increased Range Wireless Power Transfer

Abstract: The ability to wirelessly power electrical devices is becoming of greater urgency as a component of energy conservation and sustainability efforts. Due to health and safety concerns, most wireless power transfer (WPT) schemes utilize very low frequency, quasi-static, magnetic fields; power transfer occurs via magneto-inductive (MI) coupling between conducting loops serving as transmitter and receiver. At the “long range” regime – referring to distances larger than the diameter of the largest loop – WPT efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 23 publications
2
102
0
1
Order By: Relevance
“…Actually, magnetic metamaterials have been already proposed for increasing the magnetic coupling in wireless systems in the form of magnetic lenses. This strategy requires a negative permeability material, [29][30][31][32][33] whereas our metamaterial is made of non-resonant materials with positive permeability.…”
Section: -3mentioning
confidence: 99%
“…Actually, magnetic metamaterials have been already proposed for increasing the magnetic coupling in wireless systems in the form of magnetic lenses. This strategy requires a negative permeability material, [29][30][31][32][33] whereas our metamaterial is made of non-resonant materials with positive permeability.…”
Section: -3mentioning
confidence: 99%
“…Generally, the high efficiency enhancement of WPT can be obtained using bulky MMs such as three dimensional MM slabs [15,18]. Most reported MMs in the literatures [18,20,22,23] may be too thick and large in size for applications in some occasions. In our design, the proposed WPT system has the advantages of miniaturization and ultra-thin structure compared with most early publications.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, we can use MMs to work at megahertz (MHz) band WPT systems. Recently, Urzhumov and Smith [17], Choi and Seo [18], Huang et al [19], Wang et al [20,21] and Lipworth et al [22] successively reported that efficient WPT systems can be achieved using MMs. In 2011, a theoretical analysis was presented by Urzhumov and Smith, which was about the possibility of using MM to enhance the mutual coupling between magnetic dipoles and thereby the efficiency of WPT system based on simplified assumptions [17].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of MMs, especially evanescent wave amplification, are of interest to WPT because the resonant coupling is essentially coupling of near-field evanescent waves. Very recently, theoretical analysis [9][10][11][12][13][14] and experiments [15][16][17][18][19][20][21][22] on MM to enhance the evanescent near-field and eventually improve the PTE in WPT systems have been reported. In 2010, a three-dimensional (3D) MM with a relative permeability equal to −1 was proposed by Choi and Seo [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that this MM structure was used as a magnetic flux guide in order to enhance the efficiency of energy transmission between a source and distant receiving coil. Urzhumov and Smith presented a theoretical analysis on the possibility of using MMs to enhance the mutual coupling between magnetic dipoles and thereby the efficiency of WPT system based on simplified assumptions [9,11]. Wang et al [16] showed that MM could be utilized to enhance the evanescent-wave coupling for enhancing power transfer.…”
Section: Introductionmentioning
confidence: 99%